2010
DOI: 10.1002/lsm.20885
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy of a fractional resurfacing device

Abstract: Background and Objective: Recently, there has been much debate regarding the long-term efficacy of fractional resurfacing devices. While pulsed CO 2 laser resurfacing is considered a highly effective treatment, fractionated resurfacing is a newer modality and its long-term efficacy has yet to be assessed. We report the long-term outcomes of subjects previously treated with fractional CO 2 resurfacing for photodamaged skin and acne scars. Study Design/Materials and Methods: Ten subjects from our previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 3 publications
6
52
0
2
Order By: Relevance
“…Since then, AFCL has been used for resurfacing of the face with significant results and acceptable safety profile (13)(14)(15)(16)(17), but caution has been considered for non-facial areas such as neck, chest and hands due to the possibility of delayed wound healing and abnormal scarring (18,19). Therefore, the efficacy and safety of AFCL in hand resurfacing has been studied less frequently until 2011, when Stebbins and Hanke (11) reported AFCL resurfacing as a highly tolerable, safe, and efficient modality in hand resurfacing.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, AFCL has been used for resurfacing of the face with significant results and acceptable safety profile (13)(14)(15)(16)(17), but caution has been considered for non-facial areas such as neck, chest and hands due to the possibility of delayed wound healing and abnormal scarring (18,19). Therefore, the efficacy and safety of AFCL in hand resurfacing has been studied less frequently until 2011, when Stebbins and Hanke (11) reported AFCL resurfacing as a highly tolerable, safe, and efficient modality in hand resurfacing.…”
Section: Discussionmentioning
confidence: 99%
“…Oritz et al assessed the long-term outcomes in ten subjects previously treated with fractional CO 2 resurfacing for treatment of acne scarring and photodamage who returned for long-term follow-up visits at 1 and 2 years, respectively [66]. Investigators graded the maintenance of improvement on a quartile scale based on clinical photo graphy.…”
Section: Fractional Lasersmentioning
confidence: 99%
“…Long-term effi cacy was assessed by Ortiz et al ( 2010 ) who evaluated 10 subjects at 1 and 2 years after fractional CO 2 treatment of acne scarring and photodamage in the face. Investigators graded maintenance of improvement on a quartile scale based on clinical photography and found that subjects maintained 74 % of their overall improvement at their long-term visits compared to 3-month follow-up visits.…”
Section: And 1292 )mentioning
confidence: 99%